Typology of Methods on Inter-Maghrib-Isha Al-Quran Learning at TPQ Al-Ittihad and TPQ Assa'adah Muara Tebo - Jamil, Helmun (Indonesian Journal of Islamic Education and Local Culture, 2024)
Choosing a Qur’anic method of learning is very important for the younger generation who are trying to be able to read the Holy Book correctly. Researchers in this case are interested in studying alternative religious education, namely Inter-Maghrib-Isha Al-Quran Learning as an effort to eradicate Koran illiteracy for children and teenagers. The research aim is to: (1) Describe the typology of Al-Quran learning methods used in recitation between Maghrib-Isha at TPQ Al-Ittihad and TPQ As-Sa'adah Muara Tebo, (2) describe the impact of using the method on students' success in each TPQ. To achieve the above objectives, descriptive qualitative research approach is used. Data collection methods through observation, interviews and documentation. And checking the data validity is by using triangulation. The results of the research are: (1) Al-Quran learning at TPQ Al-Ittihad uses the Iqro' method, one of the well-known methods used in various recitations between Maghrib and Isha throughout the country. Meanwhile, TPQ As-Sa'adah prefers to use the Tilawati method which is no less famous in Indonesia. (2) The two methods used in the two TPQs have so far had a positive impact, marked by the students' ability to recognize Al-Qur'an letters, students’ confident, and teachers’guidelines in learning quality improvment. Keywords: typology; method; inter Maghrib-Isha Qur’anic learning